Organizational behavior - Hellriegel, Don.; Slocum, John W. (Mason, Ohio : Thomson / South-Western, 2004)
Organizational Behavior, 10th edition presents classic and emerging organizational behavior trends and research, making the subject both accessible and meaningful for learners. To make the connection between theory and practice, the authors include timely examples, exercises, and high-interest cases. To help learners focus and understand the importance of organizational behavior, the authors introduce seven managerial competencies that are essential to being an effective leader or member of an organization. These competencies are introduced early and woven throughout in special features, exercises, and an interactive self-assessment tool.
Learning About Organizational Behavior -- Individuals in Organizations -- Understanding Individual Differences -- Understanding Perceptions and Attributions -- Fostering Learning and Reinforcement -- Motivation in the Workplace -- Motivating Individuals for High Performance -- Managing Individual Stress -- Team land Leadership -- Managing Teams -- Managing Interpersonal Conflict and Negotiation -- Leading Effectively: Foundations -- Leading Effectively: Contemporary Developments -- Fostering Interpersonal Communication -- The Organization -- Making Decisions in Organizations -- Designing Organizations -- Cultivating Organizational Culture -- Guiding Organizational Change Integrating Cases.
Includes bibliographical references and index.
1
Keywords: Organizational behavior